Revealing the mechanisms of irreversible fouling during microfiltration – The role of feedwater composition. Issue 2 (April 2022) - Gupta, Kunal; Chellam, Shankararaman
Abstract: While microfiltration has seen wide acceptance in water treatment, the irreversible fouling of microfilters remains as the biggest impediment to their long-term performance. Thus, developing a better understanding of the mechanisms of irreversible fouling is crucial. To this end, we investigated the mechanism of effluent organic matter (EfOM)-membrane interactions responsible for irreversible fouling of polyvinylidene fluoride (PVDF) microfiltration membranes during wastewater effluent filtration by evaluating the backwash efficacy of different backwashing solutions (ultrapure water, NaCl, CaCl2, HCl, NaOH, and NaClO). The backwash efficiency followed the order HCl < salt solution ≈ Ultrapure water < NaOH < NaClO. A combined analysis of these results suggests that electrostatic interactions (divalent cation influenced EfOM-membrane bridging) play a minimal role in effecting irreversible fouling and non-electrostatic direct EfOM-membrane interactions like hydrophobic interactions dominantly influence irreversible fouling. Since model organic matter species (bovine serum albumin, alginate, and humic acid) are regularly used to simulate wastewater effluent, we also evaluated the mechanism of irreversible fouling during filtration of model organic matter solution using salt solution backwashing. The efficiency followed the order – CaCl2 < Ultrapure water < NaCl, indicating electrostatic interactions as the dominant fouling mechanism. Thus, results from lab-scale studies employing model organic matter species should be interpreted cautiously and conservatively. Graphical Abstract: ga1 Highlights: EfOM-membrane specific interactions dominantly influence irreversible fouling. NaClO-CEB led to effective fouling reversal during wastewater effluent filtration. Salt backwashing exacerbated irreversible fouling compared to ultrapure water. Different fouling mechanisms with wastewater effluent and model foulants.